IGRAHIM FROM URADA AND HIS COLLECTION OF MANUSCRIPTS - Sihsaidov, A R (History, Archeology and Ethnography of the Caucasus, 2015)
The article is devoted to the thematic characteristics of the manuscript collection of Ibragim Uradinsky, the famous scholar, madrasah teacher, one of the main organizers of the struggle of the Dagestan people against Nadir-Shah’s hordes, rushed into Dagestan in the middle of the 18th century.